2020
DOI: 10.3389/fpubh.2020.00297
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress and Low-Back Pain Among Healthcare Workers: A Multi-Center Prospective Cohort Study

Abstract: This study aimed to investigate the association between perceived stress and odds of low-back pain (LBP) in a population of Danish healthcare workers. Methods: Utilizing a prospective cohort design with 1-year follow-up, a total of 1,944 healthcare workers from 389 departments at 19 hospitals responded to questionnaires containing items related to lifestyle, health, and working environment. Using Cohen's Perceived Stress Scale, associations between baseline stress levels and LBP intensity (0-10 scale) at follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
32
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 54 publications
10
32
1
1
Order By: Relevance
“…The results of the present study were similar to those of previous research regarding the association between psychological stress and pain [8][9][10][11]14 . Most such studies identified associations by sampling from specific occupation groups, such as eldercare, emergency care, and healthcare workers [8][9][10] .…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present study were similar to those of previous research regarding the association between psychological stress and pain [8][9][10][11]14 . Most such studies identified associations by sampling from specific occupation groups, such as eldercare, emergency care, and healthcare workers [8][9][10] .…”
Section: Discussionsupporting
confidence: 91%
“…10,16,17 This might be attributed to an increased risk of negative health outcomes resulted from workrelated stress. 35 Emotional exhaustion, high emotional demands, and poor psychosocial safety climate are some indicators of stress which significantly intensify the risk of musculoskeletal pain including LBP. 36 Bank workers who did not perform physical activity were nearly three times at higher risk of developing LBP than bank workers who perform physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…42 The lower back was also the most affected Jakobsen, and Andersen (2020) study. 45,58,59,65 Further evidence of lower back pain among nurses, in support of the present study findings, was found in Chanchai et al (2016) study among nurses in Thailand, whereby the lower back was the most affected body region among nurses. 47 Ouni et al (2020) descriptive study also revealed that the lower back was the most affected body region among Tunisian nurses.…”
Section: Years Of Employmentsupporting
confidence: 88%
“…The nurses responded to questionnaires with items on lifestyle, health, and working environment, and the study findings indicated that moderate and high stress at baseline increased the odds of LBP at one year follow up with odds ratios (OR) of 1.39 (95% CI 1.13-1.71) and 1.99 (95% CI 1.49-2.66) respectively. The researchers concluded that psychological stress increases the odds of LBP among healthcare workers, and similar findings were found in the cross-sectional study done by Hammig (2020) 63,65. Al-Hadidi et al (2020) carried out a cross-sectional study on the prevalence of LBP among female Jordanian Hospital staff at childbearing age since low back…”
mentioning
confidence: 60%